Polimorfismo por Random Amplified Polymorphic DNA (RAPD) em metacestódeos de Taenia solium provenientes de diferentes áreas geográficas do Brasil e a reatividade de anticorpos IgG séricos de pacientes com neurocisticercose frente aos isolados obtidos - Barcelos, Ivanildes Solange da Costa (2006)
Neurocysticercosis (NC) is a polymorphic disease and the immune response in human carrier is heterogenic. In this study, 35 primers were used for amplifications by Random Amplified Polymorphic DNA (RAPD) of Taenia solium metacestodes, from five different geographic areas in Brazil: 1) Distrito Federal (DF), Center West; 2) Barreiras (BA), Northeast and Southeast; 3) Hydro Basin of the Mosquito River (North of Minas Gerais, RM-MG), 4) São Paulo (SP) and 5) Uberaba (Minas Gerais, UB-MG). Metacestodes saline crude extracts of four populations (DF, BA, RM-MG e SP) were used for the detection of specific IgG antibodies by ELISA and Western Blotting (WB). A total of 157 serum samples of three groups, (G1): 49 NC patients; (G2): 68 patients with other helminthiasis: hydatidosis (10), taeniasis (20), strongyloidiasis (20), schistosomiasis (10) and hymenolepiasis (8); and (G3): 40 healthy individuals; were analyzed by ELISA. From these, the 98 serum samples were assayed by WB; G1 (49), G2 (39) and G3 (10). The genetic distances, in disagreement percentage, between the metacestode populations were calculated from of 15 RAPD markers and showed 49.5% (DF), 48% (BA), 38.5% (UBMG) and 28% (RM-MG and SP) of genetic distances. Six primers identified polymorphic fragments and the primers 26 (GGGTTTGGCA) and 29 (TCGCCAGCCA) allowed a better differentiation of populations. The fragments of 1000, 500 and 326 pb (pairs of bases) in the UB-MG and of 600 and 244 pb in RM-MG were amplified by primer 26. The fragments generated by primer 29 were 500, 800 and 1191 pb, 300 and 1377 pb, 1000 pb and 244 and 434 pb in SP, UB-MG, DF and BA populations, respectively. In G1, the positivity by ELISA was: 90% (DF), 69% (BA), 71% (MG) and 67% (SP). The DF extract was more antigenic than others (p=0.02). In WB, the 64-68 kDa antigens were recognized in all extracts, exclusively, in serum samples from active NC patients (p=0.001). Variation in banding pattern was detected between the extracts (p<0.05). In G2, the serum samples of hydatidosis patients presented from 70 to 90% positivity by ELISA in antigenic extracts (p<0.05); however, the bands recognition pattern in WB was different from that presented in G1 samples. The 77 kDa band was significantly identified in hydatidosis samples (p=0.0001). In conclusion, the T. solium populations analyzed showed genetic variability and antigenic differences.